AQUATIC/SEMI-AQUATIC MACROPHYTES USED IN HERBAL REMEDIES FROM THE WETLANDS OF WESTERN ASSAM, NORTH-EAST INDIA: AQUATIC/SEMI-AQUATIC MACROPHYTES USED IN HERBAL REMEDIES FROM THE WETLANDS OF WESTERN ASSAM, NORTH-EAST INDIA - UPEN DEKA; TAPAN DUTTA; SANJAY TALUKDAR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of present investigation has been carried out for the documentation of ethnomedicinally important aquatic/semi-aquatic plants used by the rural people living in the vicinity of two major wetlands, i.e., Deepor Beel and Chandubi Beel of Western Assam, India. Methods: Intensive field surveys were conducted with the local traditional healers to gather information on medicinal plants used by them in treatment of various ailments. Results: Altogether 31 medicinal plant species belonging to 25 genera and 14 families have been documented from both the wetlands. Of 31 plant species, nine species were found to be used in skin disease, six in jaundice and liver problem, four species each in fever and urinary tract, two species in dysentery and snakebite, and remaining are found to be used in cough, stomach pain, wounds and cuts, neuralgia, toothache, tonsillitis, blood pressure, and smallpox. Conclusion: Unfortunately, the population of ethnomedicinally used macrophytes Nelumbo nucifera, Euryale ferox, and Trapa natans which are rare in these two wetlands are decreasing alarmingly due to commercial exploitation, natural as well as excessive anthropogenic pressure in these two wetlands.